CORPO TRANSEXUAL EM (IN)VISIBILIDADES DISCURSIVAS NA MÍDIA - SILVEIRA, ANDRÉIA (2017)
This dissertation arose from an event: the19 th March Gay Pride (LGBT) on Jun 07, 2015. On this day Viviane Beleboni paraded “crucified”, showing her half-naked and transsexual body, like Christ who suffered aggressions. The image of this model diffused through the social network, becoming target of criticism and insults on FaceBook besides support and identifications materialized in comments, shares and likes. In view of this event, given to seeing, reading and knowing in the media, we aim to discuss the status of the discursive event in the field of memory; And in the field of the discursive memory of images, also to understand the power relations that are inserted in the production of the subject through analysis of discourses referring to the transsexual body that erupted in the digital media. For this reason, we base on theoretical assumptions of discourse analyses of french line, thought with and from Michel Foucault. Furthermore, we have used the Historical Semiology suggested by Jean-Jacques Courtine, in order to deal about images from memory using the concept of intericonicity. Our work is justified by the need to, in the discourse field, give visibility to what has been said about these transsexual and crucified bodies that, often, they are invisible to the society, as long as, daily violence is not considered, while the representation of this suffering from Christian iconography is discursive and turned into happening of great visibility, spectacularized on social network. The analyses, both iconography and comments, pointed to the inseparable relationship with the discursive memory, clearly due to the interconnectivity. This relation with memory provided the emergence of other images of the crucifixion, which already existed, but which come to have displaced senses faced the event, We observe the body takes the central role in the objectivation discourses of the transgender person, since the relations of power are inextricably centered in their. The transsexual body is taken as an object of knowledge of various devices: the medical, the juridical, the religious, becoming subjectivated in the material of analysis as: (i) monstrous, because it violates the standards of what is understood natural; (Ii) patient updating the memory of homosexuality / transsexuality as a disease to be cured; Iii) to be demonic, since it does not belong to any of the genres socially imposed, reinterpreting the hermaphrodite figure. However, this same body is subjectivated as a martyr of the gratuitous violence that afflicts LGBT people. Thus, in the midst of this battle of speeches about the transgender person, criticisms, attacks and insults, but also words of compassion and support for the LGBT movement, we observe important relations of power that are stablished and normalize conduct, social roles and subject.